PENGARUH PINJAMAN ANGGOTA TERHADAP SISA HASIL USAHA (SHU) PADA PRIMER KOPERASI VIYATA VIRAJATI SESKOAD BANDUNG - Rosliawati; tiris sudrartono (EKBIS (Ekonomi & Bisnis), 2020)
This research is purpose to know the growth of loans members, growth of gaint net income received by members, how big influence the loans members on the against net income received by members and to find out what efforts can be made Primer Koperasi Kartika Viyata Virajati Seskoad to resolve obstacles and increase the against net income through the loans members. Techniques which was used in collecting data was questionnaire, consist of 19 questions and involving 87 respondents as sample of the research. Method which was used was descriptive quantitative method, and analysis technique was using pearson product moment, and process the data using SPSS version 25. The result of the research recaptulated of respondents answer about loans members variable (X) showed a percentage is 72% with good criteria and for against net income received by members variable (y) showed a percentage is 77% with high criteria. The result shows there is influence loans members on against net income received by members Primer Koperasi Kartika Viyata Virajati Seskoad is 47,1% which is can be seen on R square and the rest is 52,9% influenced by other factors which was not investigate by researcher with strong colerations. Researcher concludes that Primer Koperasi Kartika Viyata Virajati Seskoad Bandung has good enough at controlling loans members as a tool to influence against net income received by members However there are obstacles when interviewing are members exceeds the maximum loans limit, negligence in loans payments, and mistake in the savings and loans distributions mechanism. Researcher suggest Cooperative Primer Koperasi Kartika Viyata Virajati Seskoad Bandung computerized savings an loans writing to be more controlled, given of warning latter, and conducting credit analysis to cooperative members that will borrows.